2015
DOI: 10.1097/hjh.0000000000000675
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure variability and the development of early neurological deterioration following acute ischemic stroke

Abstract: BP variability is independently and linearly associated with the development of neurologic deterioration in acute stage of ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 37 publications
3
67
2
1
Order By: Relevance
“…And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies . And also, our findings were similar to that in the Chungs' study . Both studies suggested that the acute in‐hospital BPV was strongly associated with the risk of having a END.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies . And also, our findings were similar to that in the Chungs' study . Both studies suggested that the acute in‐hospital BPV was strongly associated with the risk of having a END.…”
Section: Discussionsupporting
confidence: 92%
“…Studies had demonstrated that increased BP in the acute stage of ischemic stroke may be associated with poor functional outcome because there is augmentation of cerebral edema, hemorrhagic transformation, or stroke recurrence . In addition, variability of BP in the acute stage of ischemic stroke is also reported to be associated with stroke outcome with respect to mortality, lesion growth on diffusion‐weighted MRI, functional outcome, and symptomatic hemorrhagic transformation . In this study, BPV was proved to be related to the development of END in patients with acute minor stroke or TIA due to steno‐occlusive arterial disease.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We did not measure the correlation between clot burden and presenting BP and their impact on the final outcome. Also, we did not assess other components of BP including pulse pressure, mean arterial pressure, and (more specifically) BP variability, which has been associated with early neurological deterioration in patients with AIS 26. Moreover, we did not record serial BP measurements after admission and the variability of BP levels prior to and during EVT, and consequently we were unable to assess the potential impact of periprocedural BP fluctuations on stroke outcome.…”
Section: Discussionmentioning
confidence: 99%
“…6 Farooq & Gorelick Blood pressure variability in acute stroke patients with intracranial atherosclerotic occlusive disease may be associated with neurologic deterioration and poor neurologic outcome. 7 Therefore, augmentation of BP and reduction of BP fluctuations in the acute setting may be useful, especially when auto-regulatory mechanisms are compromised in the area of cerebral infarction and the surrounding penumbra. The penumbra may be thought of as a shadow zone of compromised cerebral blood flow or perfusion in which brain tissue is rendered ischemic and dysfunctions, but frank infarction has not occurred.…”
Section: Discussionmentioning
confidence: 99%